Inheritance of Flower Size in Petunia Hybrida L. - KAMEL, H. A.; SALLAM, SAMIR; MISIHA, A.; HUSSEIN, H. A. (The Libyan Journal of Agriculture, 2023)
The present investigation was carried out to study the genetic system controlling flower size in Petunia hybrida. Five different pure lines of Petunia hybrida were entered in a 5 x 5 daillel cross. Methods of analysis proposed by Hayman (3) and Mather and Jinks (5) were used. The results obtained are summarized as follows: 1. This character is controlled by an additive-dominance polygenic system. The contributions of additive gene actions to the genetic variance were sulatively lower than the contribution of dominance. 2. The dominance was ambidirectional. 3. The number of genes (or gene groups) controlling the character was about 5. Heritability estimates was 0.89 in the broad sense and 0.37 in the narrow sense. 4. Heterosis expressed as percent increase of the mean of Fj above the higher parent was observed and ranged between -I- 2.6 to + 16%.